2015
DOI: 10.1001/jamainternmed.2015.42
|View full text |Cite
|
Sign up to set email alerts
|

Continuous Proton Pump Inhibitor Therapy and the Associated Risk of RecurrentClostridium difficileInfection

Abstract: IMPORTANCE Clostridium difficile infection (CDI) is associated with significant morbidity, mortality, and a high risk of recurrence. Proton pump inhibitor (PPI) use is associated with an initial episode of CDI, and PPIs are frequently overprescribed. For many, the use of PPIs could likely be discontinued before CDI recurrence. OBJECTIVES To determine whether PPI use was associated with a risk of initial CDI recurrence, to assess what proportion of patients who developed CDI were taking a PPI for a non-evidence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
159
2
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 205 publications
(165 citation statements)
references
References 33 publications
2
159
2
2
Order By: Relevance
“…Thus far, widespread evidence has revealed that various factors predictive of rCDI-similar to those already mentioned for CDI-are suspected of microbiome modulation, including PPIs, antibiotic re-exposure after CDI treatment, fluoroquinolone use, appendectomy, surgery, chemotherapy, low immunoglobulin levels against C. difficile toxin A or B, age, and infection with hypervirulent B1/NAP1/ribotype 027 strains [45][46][47][48][49][50][51]. Other risk factors include the presence of an ileal pouch [52], fecal incontinence, and concomitant antacid use and hypoalbuminemia [47,[53][54][55].…”
Section: Recurrent C Difficile Infection (Rcdi)mentioning
confidence: 92%
See 1 more Smart Citation
“…Thus far, widespread evidence has revealed that various factors predictive of rCDI-similar to those already mentioned for CDI-are suspected of microbiome modulation, including PPIs, antibiotic re-exposure after CDI treatment, fluoroquinolone use, appendectomy, surgery, chemotherapy, low immunoglobulin levels against C. difficile toxin A or B, age, and infection with hypervirulent B1/NAP1/ribotype 027 strains [45][46][47][48][49][50][51]. Other risk factors include the presence of an ileal pouch [52], fecal incontinence, and concomitant antacid use and hypoalbuminemia [47,[53][54][55].…”
Section: Recurrent C Difficile Infection (Rcdi)mentioning
confidence: 92%
“…Specifically, McDonald and colleagues found cause-specific hazard ratios for rCDI of 1.5 (95 % CI 1.1-2.0) for continuous PPI and 1.3 (95 % CI 0.9-1.7) for antibiotic re-exposure [45]. Deshpande et al identified the use of PPI (RR 1.58; 95 % CI 1.13-2.21; P = .008) as the most frequent independent risk factor associated with rCDI, together with age greater than 65 years (RR 1.63; 95 % CI 1.24-2.14; P = .0005), additional antibiotics during follow-up (RR 1.76; 95 % CI 1.52-2.05; P \ .00001), and renal insufficiency (RR 1.59; 95 % CI 1.14-2.23; P = .007) [57].…”
Section: Recurrent C Difficile Infection (Rcdi)mentioning
confidence: 99%
“…16 Recent observational studies indicated that it is not only antibiotic use, but also PPI use, that is associated with increased risk of Clostridium difficile infection. 5,17 Subsequent gut microbiota studies attributed the increased risk to unfavorable gut microbiota alterations caused by PPI use. [6][7][8] Human, animal and in vitro studies show an overlap between the specific gut microbiota alterations associated with PPI use (as found in Imhann et al Gut 2016) and the bacterial changes that lead to increased susceptibility to Clostridium difficile (as depicted in Fig.…”
Section: Consequences Of Gut Microbiota Changes Caused By Medicationmentioning
confidence: 99%
“…25 Since PPIs are often prescribed, and these prescriptions renewed, without evidence-based indication, a reduction of unnecessary PPI use could also contribute to this aim. 17 PPI are also associated with an increased risk of other enteric infections caused by Salmonella, Shigella and Campylobacter species. 4 In the Netherlands, recent trends toward increased incidence of campylobacter infections closely follow trends in the number of PPI prescriptions: both increased rapidly from 2004 to 2011 then showed small decrease in 2012.…”
Section: Consequences Of Gut Microbiota Changes Caused By Medicationmentioning
confidence: 99%
“…This illustrates the importance of colonization resistance as a body-surface effect of protective immunity, which sets a higher threshold for the doses of infective enteric pathogens such as Salmonella and Shigella, and probably explains the clinical effectiveness of stool transplantation in patients with recurrent infections of Clostridium difficile in which repeated doses of antibiotics have failed (van Nood et al 2013). The concept of colonization resistance is not restricted to preventing a pathogen from initially establishing itself and penetrating host tissues, as postinfective restoration of microbiota diversity is necessary to clear pathogenic bacteria (Endt et al 2010;McDonald et al 2015;Imhann et al 2016). …”
Section: Do the Microbiota Influence Protective Immunity To Pathogens?mentioning
confidence: 99%